Effects of docking and fattening period on growth and carcass composition of Lori-Bakhtiari male lambs. - Talebi, M.A. (Malaysian Society of Animal Production, 2014)
The data of sixty Lori-Bakhtiari single male lambs were assigne to a completely randomized design with two factors tail status and fattening period and docking on feedlot performance and carcass composition. Lambs were weaned at 90+ 5 days of age and were divided randomly into three groups 75, 90 and 105 days of feedlot while being kept in individual boxes. At the end of fattening period half of lambs of each level treatment were slaughtered randomly. The results showed that daily weight gain (DWG), final weight (FW) and total weight gain (TWG) during the fattening period were influenced by tail status. Docked lambs were significantly superior in DWG, FW, TWG and feed conversion (CF) as compared to undocked lambs. The lenght of the fattening period had significant effect on gain and FW, but did not influence on DWG and FC during the fattening period. The percentage of the carcass meat, subcutaneous and internal fat docked lambs were significantly higher than in the undocked ones. Total carcass fat docked lambs were 5.3% lower than intact lambs, that this different between two groups were statistically significant. Carcass weight significantly increased with the increase in the fattening period. This was accompanied by of non-significant increase in the percentage subcutaneous fat, internal fat and total carcass fat and a non-significant decrease in the percentage of meat.